Mn(IV), Co(II) and Ni(II) complexes of the Schiff bases of 2-hydroxy-naphthaldehyde with amino alcohols: synthesis, characterization and electrochemical study; DFT study and Catecholase activity of Mn(IV) complex. Issue 20 (11th October 2020) - Sagar, Shipra; Parween, Arfa; Mandal, Tarun K.; Lewis, William; Naskar, Subhendu
Abstract: Four new mononuclear complexes, [Mn IV (L 1 )2 ] (1 ), [Co II (HL 1 )2 ] (2 ), [Ni II (HL 1 )2 ] (3 ), and [Ni II (HL 2 )2 ] (4 ), with ligands H2 L 1 (2-hydroxyethylimino)methylnaphthol) and H2 L 2 (3-hydroxy propylimino)methylnaphthol) have been synthesized, characterized, and their catecholase activities have been studied. Single-crystal X-ray diffraction study shows that 1 crystallizes in P43 21 2 space group and adopts an octahedral geometry in meridional fashion, whereas 4 with a square planar geometry crystallizes in P21 /n space group. The catecholase activity has been investigated in acetonitrile by UV-Vis spectrophotometric technique. The kinetic study revealed that 1 has a moderate catecholase activity ( k cat = 812 h −1 ), whereas 2 –4 are inactive. Electronic structure of 1 and 4 has been established by theoretical calculation. Structures of both complexes have been optimized by DFT. Experimental electronic spectra of the complexes have been corroborated by TD-DFT analysis. Graphical Abstract: